Midline Suboccipital Subtonsillar Approach in Semisitting Position for Resection of Jugular Tubercle Meningioma: 2-Dimensional Operative Video - Lieber, Stefan (J Neurol Surg B Skull Base, 2021)
We present a case of a large jugular tubercle meningioma that was removed through a midline suboccipital subtonsillar approach in semisitting position. The patient is a 49-year-old woman with chronic, medication-resistant cephalgias but devoid of any subjective focal neurological deficit. On magnetic resonance imaging (MRI), an extra-axial lesion, originating from the left jugular tubercle was discovered. There was significant obliteration of the peripontine cisternal space, and compression of the adjacent pontomedullary junction; the lesion also extended into the left jugular foramen. On physical exam, an absent gag reflex was noted on the left, as well as a moderate deviation of the uvula to the contralateral side (partial Vernet's syndrome). A gross-total resection was achieved, histopathology confirmed a World Health Organization (WHO) grade I angiomatous meningioma with a low-proliferation index. The patient was discharged home 4 days after surgery with intact function of the lower cranial nerves (CN) following immediate and complete resolution of the preexisting partial CNs IX and X deficits. At 2-year follow-up, there was no indication of intradural residual or recurrence. In summary, the midline suboccipital subtonsillar approach is a simple and effective tool with limited morbidity in the armamentarium for the microsurgical management of pathologies residing in the posterior cranial fossa or the craniocervical junction. Major limitations exist for lesions extending above the internal acoustic canal or those of fibrous consistence featuring widespread adhesion to the ventral brainstem or vascular encasement. Provided the necessary anesthesiological precautions and intraoperative procedures the semisitting position is safe and effective. The link to the video can be found at: https://youtu.be/bbVXagwhDCo .